Research on Didactics of Translation and Interpreting in Graduate Programs in Translation Studies - Rodrigues, Carlos Henrique (TradTerm, 2024)
This paper presents a mapping of Brazilian research carried out within the scope of Graduate Programs in Translation Studies, from 2005 to 2020, considering the field of Didactics of Translation/Interpreting. Based on its systematization and analysis, it is found that the production corresponding to Didactics of Translation/Interpreting, in Brazilian Graduate Programs in Translation Studies, remains limited; since if we consider the total number of 701 research studies mapped, only 19 of them (2.7%) — 10 dissertations and 9 theses — are related to this field.